Análise geoespacial para estimativa da produtividade da piscicultura de tilápia na microrregião de Toledo - Moraes, Antonio Jose Sousa de (2023)
The objective of this work was to carry out a spatial analysis of tilapia productivity in fourteen municipalities in the western region of Paraná, specifically in the micro-region of Toledo, using the Geographic Information System (GIS). The study was conducted from March to October 2022, using the QGIS 3.4.8 software. A total of 9,024 excavated ponds were mapped and vectorized, representing a total area of 2,863.21 hectares of water depth. These nurseries were classified into four size categories: micro (smaller than 1,000 m²), small (1,000 m² to 3,999 m²), medium (4,000 m² to 6,999 m²) and large (larger than 7,000 m²). To calculate productivity, only excavated nurseries with an area of 1,000 m² or more were considered. An average density of 7 fish/m², average final weight of 0.9 kg/m² and average cultivation duration of 250 days were adopted, with average yields of 94.5 tons/ha/year. A production of 212,075.41 tons of tilapia per year was estimated in the fourteen municipalities of the Toledo microregion, taking into account only the productive ponds during the mapping period.